Dilatory effects and safety of a polyphenol-rich extract of Steganotaenia araliacea Hochst (Apiaceae) on rat aortic rings - Simfukwe, Newton; Prashar, Lavina; Nyirenda, James; Goma, Fastone Mathew; Ezeala, Christian Chinyere (Frontiers in Pharmacology, 2025)
BackgroundHypertension is a major global public health concern. Many communities in developing countries still rely on medicinal plants as a source of primary healthcare for treatment of hypertension instead of conventional antihypertensive drugs. Steganotaenia araliacea is traditionally used to treat hypertension, but no scientific study has been conducted to prove its efficacy; hence, we carried out this work.Aims of the studyThis study evaluated the vasorelaxant effect of a phenolic-rich extract from the roots of S. araliacea on isolated rat aortic rings.MethodsFresh roots of S. araliacea collected from Chongwe district, Zambia, were dried and ground to fine powder, and polyphenols were extracted by maceration. An ex vivo experiment was carried out to test the S. araliacea polyphenol-rich extract (SAPE) on isolated rat aortic rings. Isometric tension measurements on the aortic rings were evaluated to study the vasodilatory effects using the tissue/organ bath and the PowerLab data acquisition system. Phenylephrine (PE) was used for pre-contraction of the aortic rings, and cumulative concentrations (0.2 mg/mL to 16.91 mg/mL) of SAPE were tested to antagonize the aortic contraction. Acetylcholine (ACh) and sodium nitroprusside (SNP) served as the standard drugs for inducing dilatory effects against PE. L-nitro-arginine-methyl-ester (L-NAME) was applied to block endothelial nitric oxide synthase (eNOS) activity for establishing the possible involvement of the NO/cGMP mechanism of action.ResultsThe total polyphenol content ranged from 952 ± 3.40 mg gallic acid equivalent (GAE/100 g) to 97.8 ± 1.20 mg GAE/100 g of dry extract. The methanolic extract induced significant dilatory effects on the endothelium intact and denuded aortic rings, with the maximum percentage relaxation of 98.9% ± 0.714% and 97.29% ± 3.34%, respectively. The median IC50 values were 5.07 ± 1.05 mg/mL and 5.56 ± 1.08 mg/mL, respectively. Vasodilatory effects were significantly reduced in the presence of L-NAME, with p value < 0.05. The aqueous root extract was found to be practically nontoxic at a concentration of 10,000 mg/kg in mice.ConclusionThis study demonstrated that the polyphenol-rich extract of S. araliacea produces significant vasodilatory effects, demonstrating potential to act as an antihypertensive agent. Further studies are needed to validate these findings.